Gastric cancer presenting with ramucirumab-related gastrocolic fistula successfully managed by colonic stenting: a case report - Hiroki Fukuya; Yoichiro Iboshi; Masafumi Wada; Yorinobu Sumida; Naohiko Harada; Makoto Nakamuta; Hiroyuki Fujii; Eikichi Ihara (Clinical Endoscopy, 2023)
We report a rare case of gastric cancer presenting with a gastrocolic fistula during ramucirumab and paclitaxel combination therapy that was successfully managed with colonic stenting. A 75-year-old man was admitted to our hospital with the chief complaint of melena. Esophagogastroduodenoscopy revealed a large ulcerated tumor in the lower stomach, judged by laparoscopy as unresectable (sT4bN1M0). After four cycles of first-line chemotherapy with S-1 plus oxaliplatin, the patient showed disease progression, and second-line therapy with ramucirumab and paclitaxel was started. At the end of the third cycle, the patient had gastric antral stenosis, which necessitated the placement of a gastroduodenal stent. When the patient complained of diarrhea 10 days later, esophagogastroduodenoscopy revealed a fistula between the greater curvature of the stomach and the transverse colon. The fistula was covered by double colonic stenting, with a covered metal stent placed within an uncovered metal stent, after which leakage from the stomach to the colon stopped.